Research Trends of Waste Heat Recovery Technologies: A Bibliometric Analysis from 2010 to 2020 - Pena, Alfonso Rodríguez; Cambronel, Daniel Maestre; Ochoa, Guillermo Valencia; Henríquez, Lisandro Vargas (International Journal of Energy Economics and Policy, 2022)
Waste heat recovery (WHR) technologies have become vital to promote efficient operation in energy systems. The present investigation presents a bibliometric analysis of the research trends in the WHR field in the last decade (2010-2020). The study implements advanced methodologies to gather relevant information for interested readers on this topic. Results indicated that WHR technologies have registered more than 14,000 articles in the selected timeline with an increasing tendency. Moreover, the number of citations escalated to more than 25 % in 2020, using 2010 as the baseline. Three primary research clusters stated that power cycles are the most cited topic in the WHR field. The journal “Energy” featured the highest citation margin, whereas the most relevant author from the database was Adrian Bejan. Lastly, China is leading the progress in the number of articles and subsequently the citation score, which is primary promoted by the “Chinese Academy of Science”. The study identified that the reduction of citations of WHR topics in the last 5 years might be primarily attributed to a transition in a more complex concept of multigeneration. In conclusion, the area of WHR technologies has maintained an increased interest in academia in the last 10 years while contributing to the exploitation of power cycle proposals, turbomachinery, heat exchangers, among others. Also, WHR plays a central role in the development of the next generation of multigeneration units.